Electromagnetic therapy for treating pressure ulcers. - Aziz, Z.; Flemming, K.; Cullum, N.A.; Olyaee Manesh, A. (2010)
The results provide no strong evidence of benefit in using EMT to treat pressure ulcers. However, the possibility of a beneficial or harmful effect cannot be ruled out because there were only two included trials, both with methodological limitations and small numbers of participants. Further research is recommended.